Nucleoterpenes of Thymidine and 2′‐Deoxyinosine: Synthons for a Biomimetic Lipophilization of Oligonucleotides. Issue 1 (22nd January 2013) - Köstler, Karl; Werz, Emma; Malecki, Edith; Montilla‐Martinez, Malayko; Rosemeyer, Helmut
Abstract 2′‐Deoxyinosine (1) and thymidine (7) were N‐alkylated with geranyl and farnesyl moieties. These hydrophobic derivatives, 3a and 3b, and 9a and 9b, respectively, represent the first synthetic biomimetic nucleoterpenes and were subsequently 5′‐protected and converted into the corresponding 3′‐O‐phosphoramidites, 5a and 5b and 11a and 11b, respectively. The latter were used to prepare a series of lipophilized oligonucleotide dodecamers, a part of which were additionally labelled with indocarbocyanine fluorescent dyes (Cy3 or Cy5), 18–23. The insertion of the lipooligonucleotides into, as well as duplex formation at artificial lipid bilayers was studied by single‐molecule fluorescence spectroscopy and fluorescence microscopy.